Cell autonomous sonic hedgehog signaling contributes to maintenance of retinal endothelial tight junctions. (November 2017) - Díaz-Coránguez, Mónica; Chao, Daniel L.; Salero, Enrique L.; Goldberg, Jeffrey L.; Antonetti, David A.
Graphical abstract: Highlights: Cell autonomous basal activity of hedgehog signaling in retinal endothelial cells. Endogenous hedgehog signaling is required for endothelial barrier maintenance. Inhibition of hedgehog signaling with cyclopamine leads to loss of barrier properties. Cyclopamine effect is additive with VEGF to increase endothelial permeability.